An Ultra-Low Bending Loss Negative Curvature Hollow Core Fiber With a Polygon Jacketing Layer - Yun-Hao Xu; Dan-Dan Ji; Yuan-Feng Zhu; Yunqi Liu; Xingfang Luo; Hua Wang; Xiang-Yu Zuo (IEEE Photonics Journal, 2023)
We design and simulate a new type of hollow-core antiresonant fiber with the polygon jacketing layer. Through numerical calculations, the confinement loss is approximately 0.003 dB/km at 1.45 μm and the bandwidth is ∼ 410 nm @ CL < 0.1 dB/km. We found that more nested tubes can be connected to the jacketing layer to avoid the generation of more cladding nodes. The nested tube cladding with the small size of air holes can effectively suppress the coupling between the fiber cladding and core modes even at extreme bending conditions. Ultra-low bending loss is achieved, and the bending loss is lower than ∼ 0.05 dB/km @ bend radius Rb = 3 cm at 1.50 μm.